Perbankan Syariah Di Oman - Servina Rahayu; Endang Suriyani Munthe; Khaidar Rahmaini Jamila (Jurnal Ekonomi dan Bisnis Digital, 2025)
Islamic banking in Oman began to develop following the implementation of the Islamic Banking Regulatory Framework by the Central Bank of Oman in 2011. This study aims to examine the development of Islamic banking in Oman, including its history, regulations, contracts, products, and the challenges it faces. The research employs a qualitative approach using a library research method. The findings indicate that Islamic banking in Oman has experienced relatively rapid growth, supported by a strong regulatory framework and the adoption of international standards. However, the industry still faces several challenges, such as low public literacy, limited human resources, insufficient Islamic liquidity instruments, and intense competition with conventional banks. Therefore, strengthening regulations and further industry development strategies are needed to enable Islamic banking to contribute optimally to Oman’s economy.